A tutela do Direito Intelectual das criações de moda - Albano, Rita Mariana Pina Caniço (2019)
Technological evolution brought to the fashion world significant changes, especially in what concerns the speed and ease of the process of transforming the design or the model into products, in large quantities; as well as in the easy promotion and commercialization of the product, for example, through internet. These and other factors, although expanded the market, also brought negative aspects, such as the increase of counterfeiting. Additionally, technological evolution has been making it easier to produce copies of the original fashion designs and, consequently, has been increasing the risk of fashion designers’ rights to become unprotected. The present study aims to analyze how our Legislation considers and protects fashion creations and designers, within the Industrial Property Law and the Copyrights. We specifically aim to explore the boundaries between the use of a fashion design as source of inspiration, and the copy/counterfeiting of a protected fashion creation. The first part of this study introduces the theme, giving a definition of fashion design. In the second part, the author analysis the Industrial Property Law and the Copyrights’ frameworks, as means of protecting fashion design in Portugal and whether they offer to it cumulative protection. In what concerns the Industrial Property Law’s framework, the study will focus on the framework underlying the designs and models, which covers most of the fashion designs as aesthetic creations, without forgetting the framework underlying the concept of brand in fashion, the trademark or the utility model of fashion, and the residual and indirect protection from unfair competition. On the other hand, regarding the Copyrights, the study will analyze how fashion design meets the requirements to be protected within that framework, and in what consists that protection. To conclude, the study will explore the limits between fashion design as a result of inspiration from other creations, and the fashion design, which is a reproduction or a copy from an existing creation, taking into account the perspective and protection offered, not only, by the Industrial Property Law, but also by the Copyrights’ framework.